Seven new species of neotropical Malpighiaceae - Anderson, William R. (Instituto de Ecología, A.C., 2014)
Seven new species of neotropical Malpighiaceae are described: Aspicarpa steinmannii, Bunchosia breedlovei, and Bunchosia cruciana from Mexico; Bunchosia soejartoi, Lophanthera marcelae, and Mascagnia corymbosa from Colombia; and Heteropterys tiinae from Peru.